SIMILAR AND DIFFERENT ASPECTS OF THE UZBEK-ENGLISH WEDDING CEREMONIES - Sotvoldieva, Mokhinur (Educational Research in Universal Sciences, 2023)
This scientific work focuses on the similar and completely different wedding traditions of the two nations in the past and present..